2020
DOI: 10.3390/cells9061536
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Endoplasmic Reticulum Ca2+ Transporters—A Cancer Connection

Abstract: Ca2+ is an integral mediator of intracellular signaling, impacting almost every aspect of cellular life. The Ca2+-conducting transporters located on the endoplasmic reticulum (ER) membrane shoulder the responsibility of constructing the global Ca2+ signaling landscape. These transporters gate the ER Ca2+ release and uptake, sculpt signaling duration and intensity, and compose the Ca2+ signaling rhythm to accommodate a plethora of biological activities. In this review, we explore the mechanisms of activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 198 publications
0
17
0
Order By: Relevance
“…MCSs allows the efficient transfer of metabolites between compartments, particularly of calcium. The cytosol calcium concentrations are ∼100 nM ( Marchi et al, 2020 ), whereas in the ER lumen [(Ca 2+ ) ER ], it reaches 100–800 μM ( Burdakov et al, 2005 ; Zhai et al, 2020 ).…”
Section: Regulated Cellular Processes At Contact Sites and Their Relamentioning
confidence: 99%
“…MCSs allows the efficient transfer of metabolites between compartments, particularly of calcium. The cytosol calcium concentrations are ∼100 nM ( Marchi et al, 2020 ), whereas in the ER lumen [(Ca 2+ ) ER ], it reaches 100–800 μM ( Burdakov et al, 2005 ; Zhai et al, 2020 ).…”
Section: Regulated Cellular Processes At Contact Sites and Their Relamentioning
confidence: 99%
“…Depending on the context, the increase in [Ca 2+ ]i exerts either pro-apoptotic or anti-apoptotic roles [ 43 , 44 ]. For example, it was shown that CD95- or TRAIL-mediated Ca 2+ release led to apoptosis resistance due to delayed DISC formation [ 38 ] or TRAIL–DR endocytosis, respectively [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all these instances, metabolic rewiring is coupled with modifications of Ca 2+ fluxes, particularly those involving the ER Ca 2+ store ( Zhai et al, 2020 ). It has been described that pancreatic ( Okeke et al, 2016 ), breast ( Singh et al, 2017 ), colorectal ( Pierro et al, 2014 ), glioblastoma ( Kang et al, 2017 ), gastric ( Sakakura et al, 2003 ), and lung cancers ( Bergner et al, 2009 ) show increases in IP3R isoform levels, IP3R3 being the preponderant isoform ( Rezuchova et al, 2019 ; Rosa et al, 2020 ), followed by IP3R2 ( Vervloessem et al, 2014 ; Bartok et al, 2019 ).…”
Section: Implications In Cancermentioning
confidence: 99%